The In Silico Analysis and Identification of Possible Inhibitor of H5N1 Virus: Compounds Analysis and Identification of Possible Neuraminidase Inhibitors - Syafrudin, Syafrudin; Septiadi, Luhur; Alfaruqi, Nuri Thobibatus Shofia; Wahyudi, Didik; Kharisma, Viol Dhea (Future Science, 2018)
Fingerroot (Boesenbergia pandurata (Roxb.)) belongs to the family Zingiberaceae (Ginger). B. pandurata has pharmacological benefits such as neuroprotective, chemoprotective, anti-inflammatory, anti-angiogenic, antioxidant, an inhibitor of protease enzyme NS2B/NS3 dengue virus, Japanese encephalitis virus and swine flu virus (H1N1). This study aims to determine the most effective compounds from B. pandurata as neuraminidase inhibitors of H5N1 virus. The amino acid sequence for neuraminidase of avian influenza A virus subtype H5N1 of A/China/GD02/2006 was retrieved from protein sequence database at NCBI. Then, modeled by Swiss Model. Analyse of molecular docking was performed using PyRx and the interactions between neuraminidase inhibitors of H5N1 and B. pandurata active compound was analyzed by PyMol software and LigPlot+ software. From the 30 active compounds which have been docked, 4-hydroxypanduratin A, rubranine, boesenbergin B, boesenbergin A, 5,7-dimethoxyflavone, and tectochrysin had an equal or smaller free binding energy than control compound. 4-hydroxypanduratin A proved to be the most potent active compound as a neuraminidase inhibitor (NA 1) because it has the most negative binding energy and the same amino acid binding residue with the control compound. Therefore, 4-hydroxypanduratin A is predicted to be used as inhibitors of neuraminidase in the H5N1 virus.